Stress wave propagation through a 180° bend junction in a square cross-sectional bar. (1st October 2022) - Subhash, Ghatu; Garcia-Suarez, Joaquin; Cheenady, Amith; Bavdekar, Salil; Whittington, Wilburn; Molinari, Jean-Francois
Highlights: Longitudinal stress wave can flow through a 180° bend as if it were a straight rod. Long duration waves can be recovered without distortion after navigating the bend. 1-D wave propagation principles successfully describe the phenomena for long waves. Flexural waves are generated at the junction due to asymmetric deformation. The junction behaves as a low pass filter and can be used to shape the pulse. Abstract: Longitudinal elastic stress wave propagation through a 180° bend junction connecting two square bars is analyzed using analytical and numerical approaches and validated against experiments. The aim is to identify conditions under which the one-dimensional stress propagation principles can be applied to this geometry despite complete reversal of the stress wave path and study the mechanism of wave propagation through this geometry. By assuming the junction to move as a rigid body parallel to the input wave direction, the influence of the bend is analyzed for different pulse shapes and durations. For long duration stress pulses, the bend allows the stress wave to "flow" through the junction without distortion, whereas for short duration stress pulses, the wave undergoes significant dispersion. The junction behavior was further analyzed using finite element analysis and the results compared well with those of the analytical model. The wave motion through the junction results in asymmetric deformation of the junction, which generates flexural waves of different amplitudes in both the input and output bars. In general, stress pulses with constant peak amplitude and a smooth transition to the peak value suffer minimal dispersion as they traverse the junction. It is concluded that one-dimensional stress wave theory can be used to successfully model the propagation of long-duration longitudinal stress pulses around a 180° bend junction.